1993
DOI: 10.3109/10428199309087005
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy Findings in 47 Cases of Adult T-cell Leukemia/Lymphoma in Miyazaki Prefecture, Japan

Abstract: To identify factors that might improve the prognosis of adult T-cell leukemia/lymphoma (ATL), we reviewed data on 47 autopsied cases of ATL with reference to the complications and cause of death. The primary cause of death was respiratory insufficiency due to pulmonary infection. Respiratory insufficiency was also attributed to the diffuse alveolar damage and pulmonary fibrosis resulting from chemotherapy given and oxygen. About 90% of the cases had infections with one or more pathogens. Cytomegalovirus (CMV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 28 publications
2
32
0
2
Order By: Relevance
“…The most common site was spleen (85%), followed by the bone marrow (72.3%), lungs (72.3%), and gastrointestinal tract (63.8%). Adrenal gland was involved in 36.2% of the ATLL patients studied [17]. However, ATLL patients rarely present with primary and solitary extranodal NHL.…”
Section: Discussionmentioning
confidence: 99%
“…The most common site was spleen (85%), followed by the bone marrow (72.3%), lungs (72.3%), and gastrointestinal tract (63.8%). Adrenal gland was involved in 36.2% of the ATLL patients studied [17]. However, ATLL patients rarely present with primary and solitary extranodal NHL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study reviewing 47 autopsy cases of ATLL in Miyazaki Prefecture, Japan, CNS involvement developed in 4 of 35 cases examined (11.4%). 17 The relatively high reported prevalence of T-PCNSL, therefore, might be due to CNS invasion by lymphomas that originated outside of the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 47 autopsied patients with ATLL revealed that tumor cells infiltrate various organs including the spleen (85.1%), bone marrow (72.3%), lungs (72.3%), and GI tract (70.2%). In the GI tract, the stomach is most frequently involved (40.4%), followed by the colon (38.3%) and the small intestine (34.0%) [4] . Precise mechanisms for ATLL cell infiltration in GI tract have not been clarified; however, Chen et al [7] described that ATLL cells from patients with GI tract involvement showed considerably higher expression of an adhesion molecule integrin β7, suggesting a critical role of this molecule in adhesion and subsequent infiltration of a certain type of ATLL cells into intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well-known that ATLL cells infiltrate into systemic organs including gastrointestinal (GI) tract [4] , colonic involvement has not been fully documented [5] . We herein report a case of ATLL presenting MLP and provide a literature review on this rare entity.…”
Section: Introductionmentioning
confidence: 99%